Zanubrutinib Versus Bendamustine and Rituximab in Patients With Treatment-Naïve Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma: Median 5-Year Follow-Up of SEQUOIA - Shadman, Mazyar; Munir, Talha; Robak, Tadeusz; Brown, Jennifer R; Kahl, Brad S; Ghia, Paolo; Giannopoulos, Krzysztof; Šimkovič, Martin; Österborg, Anders; Laurenti, Luca; Walker, Patricia A; Opat, Stephen S; et al. (Journal of clinical oncology, 2025)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported.SEQUOIA (ClinicalTrials.gov identifier: NCT03336333) is a phase III, randomized, open-label trial that compared the oral Bruton tyrosine kinase inhibitor zanubrutinib to bendamustine plus rituximab (BR) in treatment-naïve patients with chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). The initial prespecified analysis (median follow-up, 26.2 months) and subsequent analysis (43.7 months) found superior progression-free survival (PFS; the primary end point) in patients who received zanubrutinib compared with BR. At a median follow-up of 61.2 months, median PFS was not reached in zanubrutinib-treated patients; median PFS was 44.1 months in BR-treated patients (hazard ratio [HR], 0.29; one-sided P = .0001). Prolonged PFS was seen with zanubrutinib versus BR in patients with mutated immunoglobulin heavy-chain variable region (IGHV) genes (HR, 0.40; one-sided P = .0003) and unmutated IGHV genes (HR, 0.21 [95% CI, 0.14 to 0.33]; one-sided P < .0001). Median overall survival (OS) was not reached in either treatment arm; estimated 60-month OS rates were 85.8% and 85.0% in zanubrutinib- and BR-treated patients, respectively. No new safety signals were detected. Adverse events were as expected with zanubrutinib; rate of atrial fibrillation was 7.1%. At a median follow-up of 61.2 months, the results supported the initial SEQUOIA findings and suggested that zanubrutinib was a favorable treatment option for untreated patients with CLL/SLL.
Keywords: Bendamustine Hydrochloride; dospělí; Female; pyrimidiny; Adult; ženské pohlaví; Leukemia, Lymphocytic, Chronic, B-Cell; doba přežití bez progrese choroby; bendamustin hydrochlorid; Pyrazoles; lidé; pyrazoly; Rituximab; Aged, 80 and over; následné studie; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Follow-Up Studies; Male; Aged; Piperidines; rituximab; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Progression-Free Survival; Middle Aged; piperidiny; chronická lymfatická leukemie; Pyrimidines; Humans